The "Ultimate Triple PET": 68Ga-DOTATATE, 18F-FDG, and 18F-Fluciclovine PET/CT Findings in a Single Patient With Metastatic Abdominal Carcinoid and Prostate Cancer. (13th August 2021) - McClenathan, Matthew; Peacock, Justin G.
Abstract: A 71-year-old man with a history of carcinoid and prostate adenocarcinoma underwent 68 Ga-DOTATATE PET/CT to evaluate new mediastinal lymphadenopathy. The scan revealed new carcinoid metastases, but the mediastinal nodes were not avid. 18 F-FDG PET/CT was performed to evaluate for cardiac and mediastinal sarcoidosis, revealing a lack of cardiac sarcoidosis, but probable mediastinal sarcoidosis. 18 F-Fluciclovine PET/CT was then performed for possible prostate metastases, revealing the patient's known prostate cancer. Three different PET radiopharmaceuticals revealed 3 different processes in a single patient within a 195-day period, demonstrating the power of nuclear medicine diagnostics.